2008
DOI: 10.1111/j.1745-7254.2008.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid-mediated transcriptional regulation of human GM3 synthase (hST3Gal V) in SK-N-BE(2)-C human neuroblastoma cells1

Abstract: Key wordsvalproic acid; human GM3 synthase; human n e u r o b l a s t o m a ; C R E B ; t r a n s c r i p t i o n a l regulation 1 This work was supported by a grant (M1061 9010001-08N1901-00110) from the Korea Science and Engineering Foundation (KOSEF). 6 Correspondence to Prof Young-choon LEE. AbstractAim: To investigate whether valproic acid (VPA) modulates human GM3 synthase (hST3Gal V) mRNA expression, as a part of ganglioside GM3 biosynthesis, in human neuroblastoma cells. Methods: Using RT-PCR and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(39 reference statements)
0
18
1
Order By: Relevance
“…Cell viability assay was performed as described previously [7,8,9,10,11]. The amount of formazan produced was quantified by measuring the absorbance at 490 nm with an ELISA plate reader (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability assay was performed as described previously [7,8,9,10,11]. The amount of formazan produced was quantified by measuring the absorbance at 490 nm with an ELISA plate reader (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently we studied the transcriptional regulation mechanism of human sialyltransferase genes that are specifically expressed at high levels in cell lines treated with natural compounds [7,8,9,10,11]. In the current study, we investigated the effect of physcion isolated from the Polygonum multiflorum roots on the human sialyltransferase gene expression in SK-N-BE(2)-C human neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioside GM3 expression levels were analyzed by the same procedure as described previously (6,7). Mouse anti-GM3 monoclonal antibody (mouse IgM, Kappa-chain, clone: GMR6; Seigakagu; Japan) and FITC-conjugated goat-antimouse IgM (Sigma; St. Louis, MO, USA) as the secondary antibody were used to visualize GM3 expression in ARPE-19 cells induced by VPA.…”
Section: Analysis Of Ganglioside Gm3 Expression Levels By Vpamentioning
confidence: 99%
“…These changes reflect the differential regulation of ganglioside biosynthesis catalyzed by a family of glycosyltransferases in the Golgi apparatus. Recently, we demonstrated that VPA modulates the mRNA expression of human GM3 synthase (hST3Gal V) and GD3 synthase (hST8Sia I) in human neuroblastoma cells (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of ganglioside GD3 levels on the cell membrane was carried out as described previously [16]. Briefly, SK-N-BE(2)-C, U-87MG and T98G cells were seeded on round cover slips ( pretreated with 2% of 3-aminopropyl-triethoxysilan) in an eight-well multiplate.…”
Section: Evaluation Of Ganglioside Gd3 Surface Expressionmentioning
confidence: 99%